2017
DOI: 10.1111/jog.13267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical classification and treatment of cesarean scar pregnancy

Abstract: Our clinical classification system and therapeutic strategy provide an effective and safe way to treat CSP patients resulting in reduced intraoperative bleeding, operative time, hospital days, and hospital cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…However, it was difficult to draw firm conclusions based on the 22 cases analyzed. Zhang et al classified CSP into risky and stable types, in which the risky type was further categorized into type I (Ia, Ib, Ic), type II, and type III based on the GS location and remaining myometrial thickness [ 23 ]. This classification was shown to provide a better treatment option for different types of CSP; however, this classification is somewhat complicated for most obstetricians.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was difficult to draw firm conclusions based on the 22 cases analyzed. Zhang et al classified CSP into risky and stable types, in which the risky type was further categorized into type I (Ia, Ib, Ic), type II, and type III based on the GS location and remaining myometrial thickness [ 23 ]. This classification was shown to provide a better treatment option for different types of CSP; however, this classification is somewhat complicated for most obstetricians.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, D&C was the primary treatment. Although it was performed in many cases (n = 31, CSP: 54.7%, CP: 16.7%) due to its shorter operation time, shorter hospital stay, and lower hospital cost compared to other therapeutic approaches [23], the initially unsuccessful treatment was most commonly managed with D&C [24]. Our data showed that 88.9% (8/9) of failed cases were performed by D&C. Particularly among them, 87.5% (7/8) of cases were CSP.…”
Section: Successmentioning
confidence: 99%
“…This might be a factor that the success rate of initial treatment of CP was superior to CSP (91.7% vs 84.9%). It was well-known that there were 2 types of CSP, with type 1 growing toward the uterine cavity and type 2 progressing toward the bladder and abdominal cavity [23]. D&C treatment was ideal for type 1 CSP (endogenous CSP) to completely remove the abnormally adherent trophoblastic implantation.…”
Section: Successmentioning
confidence: 99%
“…Most often, when diagnosed in the first trimester, cesarean scar pregnancies are treated with methotrexate or dilation and curettage. Expectant management is possible but it is usually associated with increased incidence of hysterectomy due to placental implantation abnormalities or uterine rupture .…”
Section: Types Of Abnormal Placentationmentioning
confidence: 99%